NEED ANALYSIS OF ENGLISH FOR PROFESSIONAL BUSINESS COMMUNICATION IN BUSINESS AND INDUSTRIAL AFFAIRS: ANALISIS KEBUTUHAN BAHASA INGGRIS UNTUK KOMUNIKASI BISNIS PROFESIONAL PADA DUNIA BISNIS DAN DUNIA INDUSTRI - Lusia Eni Puspandari; Dian Asa Utari; Miftachudin Miftachudin (LLDIKTI Wilayah X, 2024)
The ability to communicate globally, both in Indonesian and English, is extremely important in the this digital technology era. Everybody who wants to succeed in the global economy must speak English to communicate globally. In order to increase the quality of human resources, the education institutions must prepare education system or curriculum that are able to produce ready-to-use human resources. This study is aimed to analyse the need of English Competence in Professional Business Communication Industries. The data were obtained from Questionnaire and Interview with PPNS users’ companies. The result showed that the ability of using English for Professional Business Communication is one of requirements to be accomplished in order to establish modern companies that are ready to compete in the worldwide scale. It was recommended that the English for Professional Business Communication could be developed in form of study program that are prepared to accommodate the international business communication.